Menyiapkan Khotbah Berpedoman Bahasa Asli - Hasanema Wau (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2022)
Preaching is an honor, but it is also a challenging responsibility. Why? Because when preaching, one is dealing with the words and thoughts of God! Therefore, it is important for a preacher to carefully examine what the author of the text really meant. It would be a disgrace to say out loud: According to the apostle Paul or to refer to other writers and it turns out that is not what is meant. To find out the meaning of the text towards the ideal, of course, by exploring the original language of the text. The availability of various versions of the actual translation makes it easy, but it must be remembered that when the translation process takes place, the aspect of real interpretation plays a role.